A Feminist Critique of Vijay Tendulkar’s Silence! The Court is in Session - Yadav, Hitesh; George, Mercy (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Vijay Tendulkar’s Silence! The Court is in Session (1967) stands as a searing critique of the oppressive patriarchal structures embedded in Indian society, particularly the treatment of women within these systems. Through a feminist lens, this paper examines how Tendulkar dissects the hypocrisy, double standards, and malice of a society that punishes women for their autonomy and sexual expression. The play, set within the framework of a mock trial, brings to the fore the character of Leela Benare, a schoolteacher who is subjected to public humiliation and punishment for her pregnancy out of wedlock, while the male counterpart responsible for the situation remains unscathed. This paper explores how Tendulkar uses the court as a metaphor for the larger societal mechanisms that silence women’s voices and regulate their bodies, exposing the pervasive control over female sexuality. By analyzing the play’s portrayal of Benare’s eventual breakdown and the collective condemnation she faces, the study underscores the tension between individual agency and societal repression. Ultimately, this paper argues that Silence! is not merely a portrayal of personal tragedy, but a deliberate commentary on the systemic oppression of women in India, which continues to resonate with feminist concerns about the intersection of gender, power, and morality.